Estudio del movimiento superficial de un suelo multi-capas poco profundo sometido a ondas P (2016)
In this work it was designed and implemented an experimental setup to study the surface acceleration of a multilayered soil and the experimental measurements were contrasted with a one-dimensional theoretical model based on ray tracing. For this purpose, a soil was suited, where tiles and expanded polystyrene (EPS) slabs were buried. This soil was disturbed by a sound wave at normal incidence from a subwoofer. In experiment were obtained resonance frequencies which are according to the studied theoretical model. © The author; licensee Universidad Nacional de Colombia.